Enrolled Nurses' experiences learning the nurse preceptor role: A qualitative evaluation. Issue 3 (June 2017) - Ryan, Colleen; McAllister, Margaret
Summary: Background: Preceptors are crucial to the provision of effective clinical learning experiences for nursing students however many are insufficiently trained and lack support in the role. Within Australia, preceptors may work with students preparing to become Registered Nurses or Enrolled Nurses. An intervention was designed specifically to engage Enrolled Nurse preceptors because they are particularly overlooked. Methodology: A qualitative evaluation of the educational experience was undertaken using semi-structured group interviews. Findings: Four themes were identified: (a) feelings of disempowerment hinder a desire to do the job, (b) open to embracing opportunities to learn about clinical teaching, (c) barriers to engagement and (d) preceptoring across nursing divisions. Conclusion: The study identified that the learning experience was valuable. In particular participants enjoyed the challenge of engaging with digital stories where other experienced educators shared the way they responded to learning problems and developed solutions, and the facilitated discussions. Recommendations to further improve the online resource included development of stories that are relevant to the unique challenges Enrolled Nurse preceptors face.